Dual RGD-immobilized poly(L-lactic acid) by atmospheric pressure plasma jet for bone tissue engineering - GÜNDÜZ, OĞUZHAN (ELSEVIER, 2019)
Surface treatment on PLA substrates by atmospheric pressure plasma jet (APPJ) for polymerization of dual RGD-peptides were investigated. Peptide-modified surfaces have been highlighted as the most promising approach to improve the integration of implants into surrounding bones. By varying the RF power, PLA substrates treated by APPJ process have a tendency to form a hydrophobic surface. The effects on the proliferation and differentiation of MG63 cells were evaluated and osteocalcin (OCN) expression was analyzed using RT-PCR. The water contact angle of the W/APPJ process PLA was approximately 54% of that of the W/O APPJ process PLA substrates. W/APPJ process significantly increased cell proliferation, improved the functionality of the material without using a complicated procedure. We believe that pretreatment using the APPJ processes and dual RGD grafting can be more appropriate than traditional surface modification methods, with more potential for application to bone materials.
Keywords: Atmospheric-pressure plasma jet (APPJ); Osteoblast-like MG63 cells; RGD-peptides; beta-D-Glucan; Poly(L-lactic acid) (PLA); Bone tissue engineering; SCAFFOLDS; SURFACE; FILMS; BIOMATERIALS; ADHESION; PEPTIDE; BCP